Career Mapping in Software Testing: insights into the professional profile - A. Filho, José W. R.; Andrade, Francisco A.; Coutinho, Jarbele C. S.; Andrade, Wilkerson L. (Anais do Simpósio Brasileiro de Testes de Software Sistemático e Automatizado (SAST); 2025: Anais do X Simpósio Brasileiro de Testes de Software Sistemático e AutomatizadoDO - 10.5753/sast.2025.14426, 2025)
Due to the inconsistency between the professional qualifications offered in academic training and the actual demands of the software industry, entering or qualifying for a career in Software Testing can be challenging for entry-level professionals. Combined with a lack of clarity regarding the desired requirements at different career levels in this field, the industry presents a lengthy list of hard skills that are essential for a career. It emphasizes the search for mid-level or senior-level professionals, which limits the hiring process. Therefore, this study goal to identify the professional requirements expected by the industry in the field of Software Testing. Thus were conducted: (i) a qualitative and quantitative study, based on the analysis of national and international job openings posted on professional social media; and (ii) a survey of professionals with technical experience in the Software Testing sector, to validate the results obtained in the previous study. The results were organized into Junior, Intermediate, and Senior levels, and categorized according to hard skills, soft skills, academic background, and certifications. Regarding technical skills, automation tools and agile methodologies, and interpersonal skills, communication, teamwork, and leadership stand out. Finally, this study contributes to a career path mapping in Software Testing, based on insights into the actual professional qualifications required for a professional in this field.